Pengaruh Belanja Bantuan Sosial, Belanja Tidak Terduga, Belanja Barang Dan Jasa, Dan Belanja Modal Terhadap Pengelolaan Keuangan Daerah Pada Kabupaten/Kota Provinsi Sumatera Selatan - Anggi; M.Thoyib; Eka Jumarni Fithri (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
This study aims to analyze the influence of social assistance expenditures, unforeseen expenses, goods and services expenditures, and capital expenditures on the performance of regional financial management in South Sumatra Province districts/cities. This study is confined to districts and cities in the province of South Sumatra. The study relies on secondary sources for its data. South Sumatera Province Regency/City budget execution reports received from the Ministry of Finance's website provided the study's data (djpk.kemenkeu.go.id). In South Sumatera Province, 18 Regencies/Cities have recorded a total of 90 observations between 2016 and 2020. (five years). SPSS version 26 was used to analyze the data using multiple linear regression. According to the findings, social assistance expenditures, unforeseen expenses, goods and services expenditures, and capital expenditures affected the of regional financial management.